PROFESORADO, CULTURA Y POSTMODERNIDAD : CAMBIAN LOS TIEMPOS, CAMBIA EL PROFESORADO - Hargreaves, Andy (PEDAGOGIA. MANUALES, 1995)
TRADUCCION DE: CHANGING TEACHERS, CHANGING TIMES: TEACHER'S WORK AND CULTURE IN THE POSTMODERN AGE